Methyl‐donor deficiency in adolescence affects memory and epigenetic status in the mouse hippocampus. (25th March 2015) - Tomizawa, H.; Matsuzawa, D.; Ishii, D.; Matsuda, S.; Kawai, K.; Mashimo, Y.; Sutoh, C.; Shimizu, E.
Abstract: DNA methylation is one of the essential factors in the control of gene expression. Alteration of the DNA methylation pattern has been linked to various neurological, behavioral and neurocognitive dysfunctions. Recent studies have pointed out the importance of epigenetics in brain development and functions including learning and memory. Nutrients related to one‐carbon metabolism are known to play important roles in the maintenance of genomic DNA methylation. Previous studies have shown that the long‐term administration of a diet lacking essential one‐carbon nutrients such as methionine, choline and folic acid (methyl donors) caused global DNA hypermethylation in the brain. Therefore, the long‐term feeding of a methyl‐donor‐deficient diet may cause abnormal brain development including learning and memory. To confirm this hypothesis, 3‐week‐old mice were maintained on a folate‐, methionine‐ and choline‐deficient (FMCD) or control (CON) diet for 3 weeks. We found that the methyl‐donor deficiency impaired both novel object recognition and fear extinction after 3 weeks of treatment. The FMCD group showed spontaneous recovery of fear that differed from that in CON. In addition, we found decreased Gria1 gene expression and specific CpG hypermethylation of the Gria1 promoter region in the FMCD hippocampus. Our data suggest that a chronic dietary lack of methyl donors in the developmental period affects learning, memory and gene expressions in the hippocampus. Abstract : Methyl‐donor deficiency induced hyper‐methylation of Gria1 promoter in the mice hippocampus